How to Be a Speed Demon. - Wagstaff, Jeremy (Far Eastern Economic Review, 2002)
Unless a computer dates back to before the introduction of the Internet, for example, one should resist the urge to splash out on a faster processor until you have examined the many reasons that computers slow down. Computers slow down for reasons such as the condition of a hard drive, the need to add more memory, or the presence of too many programs running at the same time. However, physically replacing your computer, although it may solve some problems, does also have downsides.